Homolog of protein kinase Mζ maintains context aversive memory and underlying long-term facilitation in terrestrial snail Helix - Balaban, Pavel M.; Roshchin, Matvey; Timoshenko, Alia Kh.; Zuzina, Alena B.; Lemak, Maria; Ierusalimsky, Victor N.; Aseyev, Nikolay A.; Malyshev, Aleksey Y. (Frontiers in Cellular Neuroscience, 2015)
It has been shown that a variety of long-term memories in different regions of the brain and in different species are quickly erased by local inhibition of PKMζ. Using antibodies to mammalian PKMζ, we describe in the present study the localization of immunoreactive molecules in the nervous system of the terrestrial snail Helix lucorum. Presence of a homologue of PKMζ was confirmed with transcriptomics. We have demonstrated in behavioral experiments that contextual fear memory disappeared under a blockade of PKMζ with a selective peptide blocker of PKMζ (ZIP), but not with scrambled ZIP. If ZIP was combined with a “reminder” (20 min in noxious context), no impairment of the long-term contextual memory was observed. In electrophysiological experiments we investigated whether PKMζ takes part in the maintenance of long-term facilitation (LTF) in the neural circuit mediating tentacle withdrawal. LTF of excitatory synaptic inputs to premotor interneurons was induced by high-frequency nerve stimulation combined with serotonin bath applications and lasted at least four hours. We found that bath application of 2x10-6 M ZIP at the 90th min after the tetanization reduced the EPSP amplitude to the non-tetanized EPSP values. Applications of the scrambled ZIP peptide at a similar time and concentration didn't affect the EPSP amplitudes. In order to test whether effects of ZIP are specific to the synapses, we performed experiments with LTF of somatic membrane responses to local glutamate applications. It was shown earlier that serotonin application in such an "artificial synapse" condition elicits LTF of responses to glutamate. It was found that ZIP had no effect on LTF in these conditions, which may be explained by the very low concentration of PKMζ molecules in somata of these identified neurons, as evidenced by immunochemistry. Obtained results suggest that the Helix homologue of PKMζ might be involved in post-induction maintenance of long-term changes in the snail.